PHYSICAL AND CHEMICAL PROPERTIES OF LOCAL HONEY FROM EAST KALIMANTAN - Umul Karimah; Rika Melati; Ayu Anita Sari Ratna Saputri (BRIN Publishing, 2020)
Most of the local honey production in East Kalimantan is managed traditionally, thus honeyquality, particularly its physical and chemical properties, are unknown. However, the honey analysisSURYLGHVDFRPSUHKHQVLYHFRPSRVLWLRQSUR¿OHDQGSRWHQWLDOOhoney from East Kalimantan. This research aimed to analyse the properties of two local honeyfrom East Kalimantan. The methods used in this study were gravimetric, volumetric, spectroscopy,spectrophotometry, and chromatography. Honey A was produced by Apis cerana whereas Apis dorsataproduced honey B. The color intensities were 560±5.66 and 947.5±27.58 mAu for honey A and B,respectively. Honey A and B a had moisture content of 22.7 and 25.8% w/w, respectively. Otherproximate analysis parameters were also reported. Fructose and glucose content for honey A were30.65±2.35% w/w and 30.08±0.58% w/w, while honey B gave different pattern with fructose at28.06±1.04 and higher glucose instead at 32.74±1.13% w/w. Reducing sugar and total sugar forboth samples were higher than 60% w/w while sucrose in honey A and B were 2.8 and 1.4% w/wrespectively, thus indicating no adulteration. Vitamin C content measurement showed negligibleresult with total phenolic content of honey A was lower than honey B. Honey B had higher Na,Ca, Fe and Zn than those of honey A. This study reported thorough chemical composition of localKRQHIURP (DVW .DOLPDQWDQ LQ ZKLFK VRPH FRXOG KDYH VLJQL¿FDQW QXWULWLRQDO YDOXH +RZHYHUquality improvement particularly on moisture and reducing sugar content is necessary to meetIndonesian National Standard 8664:2018.